OS EFEITOS DAS REDES SOCIAIS NO DIREITO DA PERSONALIDADE - Oliveira, Hestéfano Christian Zeidan de; Pereira, Lavínia Larissa Paralon Souza; Castro, Micaela Alves de; Vilanova, André Bragança Brant (Sinapse Múltipla, 2020)